The role of the NF-κB, SAPK/JNK, and TLR4 signalling pathways in the responses of RAW 264.7 cells to extremely low-intensity microwaves. (April 2015) - Glushkova, Olga V.; Khrenov, Maxim O.; Novoselova, Tatyana V.; Lunin, Sergey M.; Parfenyuk, Svetlana B.; Alekseev, Stanislav I.; Fesenko, Eugeny E.; Novoselova, Elena G.
Abstract: Purpose : To investigate the role of the toll-like receptor 4 (TLR4), nuclear factor κB (NF-κB), and stress activated protein kinases/Jun N-terminal kinase (SAPK/JNK) signalling pathways in the responses of RAW 264.7 macrophages to low-intensity microwaves (MW). Materials and methods : Three inhibitors of TLR4, SAPK/JNK, and NF-κB signalling, namely CLI-095, SP600125, and IKK Inhibitor XII, respectively, were added to cultured RAW 264.7 macrophages before MW treatment. Results : MW exposure resulted in stimulation of RAW 264.7 cell activity manifested by increases in cytokine production and the stimulation of cell signalling. The blocking of a key kinase of the NF-κB pathway by IKK Inhibitor XII resulted in decreased MW-induced TLR4 expression and increased SAPK/JNK and NF-κB phosphorylation in irradiated cells. In addition, IKK Inhibitor XII significantly decreased tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin 1α (IL-1α), interleukin 6 (IL-6), and interleukin 10 (IL-10) production in both exposed and unexposed RAW 264.7 macrophages. Inhibitor SP6000125 did not prevent an MW effect on signal proteins with the exception of decreased SAPK/JNK phosphorylation in RAW 264.7 cells. Cytokine production was markedly decreased in MW-exposed cells cultured with SP6000125. The inhibitor of TLR4, CLI-095, did not affect signal proteins and cytokine production changes in MW-exposed cells. Conclusions : The results suggest that low-intensity MW promotes macrophage activity via mechanisms involving cellular signalling, particularly the NF-κB pathway.